PENGARUH PELATIHAN DAN PENDIDIKAN TERHADAP KINERJA KARYAWAN PADA PT. DEWA RENCARA PERANGIN-ANGIN (DRP) - Ella Feliyana Sitepu; Maria Sarito Doloksaribu (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2019)
Employee performance in the company affects the progress of the company because employee performance is something that is used to monitor the work productivity of human resources, both those oriented to the production of goods, and services. The purpose of this study is to analyze the effect of training and education on employee performance. Based on the results of the analysis, training and education have a positive and significant effect on the performance of employees at PT. Dewa Rencana Perangin-angin.